A Resonant Graphene NEMS Vibrometer. Issue 28 (30th May 2022) - Moreno‐Garcia, Daniel; Fan, Xuge; Smith, Anderson D.; Lemme, Max C.; Messina, Vincenzo; Martin‐Olmos, Cristina; Niklaus, Frank; Villanueva, Luis Guillermo
Abstract: Measuring vibrations is essential to ensuring building structural safety and machine stability. Predictive maintenance is a central internet of things (IoT) application within the new industrial revolution, where sustainability and performance increase over time are going to be paramount. To reduce the footprint and cost of vibration sensors while improving their performance, new sensor concepts are needed. Here, double‐layer graphene membranes are utilized with a suspended silicon proof demonstrating their operation as resonant vibration sensors that show outstanding performance for a given footprint and proof mass. The unveiled sensing effect is based on resonant transduction and has important implications for experimental studies involving thin nano and micro mechanical resonators that are excited by an external shaker. Abstract : The authors demonstrate a nano‐electromechanical resonant vibration sensor based on a graphene membrane with attached silicon proof mass. They exhibit responsivities up to six orders of magnitude larger compared to the inertial model. These excellent responsivities are due to the bending effect of the chip, which can have important implications for experimental work with nano‐ and micro‐mechanical resonators excited via external shakers.